The Numbers Gang in South African Correctional Facilities: Reflections on Structures, Functions and Culture - Veloen, Heinrich (Department of Public Law, 2023)
Prison gangs stand in a complex relationship to carceral institutions. At one level gangs on the inside of prison walls constitute a reactive and adaptive response to prisons as ‘total institutions'. But in turn, prison gangs have a formative influence on life inside the ‘total institution' – both for inmates and for prison authorities. The presence of an elaborate network of members of the so-called Numbers Gang is a well-known phenomenon in South African correctional facilities or prisons in short. The existence of the Numbers is widely associated with ongoing patterns of conflict and violence in South African prisons – between inmates and warders, between inmates, as well as between rival prison gangs. Whilst engaging the ‘problems' associated with the Numbers gang is central, rather than peripheral, to managing South African prisons according to constitutional guidelines, the Department of Correctional Services is yet to rise to the policy challenges. Substantive engagement with that policy challenge is in turn dependent on good research. This dissertation hopes to make a small contribution to that larger quest for understanding the social logic of prison gangs. This research sets out to investigate key facets of the Numbers gang in South African prisons. Drawing on my own experience of 26 years as a warden in Pollsmoor Prison in Tokai, Cape Town and on the relatively abundant academic literature on these gangs, and finally on face-to-face interviews with twenty former Pollsmoor inmates, I attempt to present an up-to-date account of the legends, the structure and operation of these gangs. This account explores the evolution of the Numbers gang; key initiation practices through which arrivals are integrated; the quasi-military command and rank structures of the three Numbers' divisions; the role and function of Sabela as a medium of communication, and the meaning of tattoos as a source of gang identification and cohesion. This account yields insights into the form, content, and impact of gangs in South African prisons. This dissertation confirms the major findings of the available literature while supplementing it with reference to contemporary developments. In particular, the dissertation draws on interviews with former Pollsmoor inmates to analyse the relationships between the Numbers Gang as a prison phenomenon, and the growing link with street gangs on the outside. Finally, the dissertation emphasises the urgency for the Department of Correctional Services to develop, refine and implement a national gang combat strategy duly informed by substantive research evidence.